Digital Activism and Protest Movements in Indonesia, Analysis of Collective Action 2014-2024 - Abdulrohim, Dodi; Budiharjo; Sukmana, Pandji; Rachmatsyah, T. Herry (International Journal of Qualitative Research, 2025)
This study examines protest dynamics in Indonesia from 2014 to 2024, analyzing patterns of collective action across five distinct actor categories: political parties, societal groups, labor unions, civil society organizations, and students. Drawing on comprehensive protest data from the Indonesian National Police, we identify key temporal patterns, triggering events, and actor-specific mobilization trends. Our findings reveal three significant protest waves (2014, 2016-2017, and 2020) corresponding to electoral cycles, economic reforms, and contentious legislation. Analysis demonstrates that different actor groups respond to distinct mobilizing factors: political parties to electoral opportunities, labor unions to economic reforms, students to democratic concerns, and civil society to governance issues. The study contributes to social movement theory by providing empirical evidence of how political opportunity structures, resource mobilization, and frame alignment manifest in an emerging democratic context. These findings enhance understanding of contentious politics in Indonesia and offer insights into the evolving nature of democratic participation in Southeast Asia.